2008
DOI: 10.1007/s11427-008-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of silkworm (Bombyx mori) sericin gene 1 and chymotrypsin inhibitor 13 using fluorescence in situ hybridization

Abstract: The chromosomal locations of two single-copy genes, Ser-1 and CI-13, in silkworm (Bombyx mori) were detected at the molecular cytogenetics level by fluorescence in situ hybridization in the study. The results showed that Ser-1 is located near the distal end of the 11th linkage group, relatively at the 12.5+/-1.4 position in pachytene; and that CI-13 has been mapped near the distal end of the 2nd linkage group, relatively at the 8.2+/-1.2 position in pachytene. Furthermore, their location model map-FISH map on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Song et al reported the chromosomal locations of two single-copy genes, Ser-1 and CI-13, in B. mori by FISH. The results showed that Ser-1 was located near the distal end of the 11th linkage group with a relative position of 12.5±1.4 in pachytene, while CI-13 was mapped near the distal end of the second linkage group with a relative position of 8.2±1.2 in pachytene [22].…”
Section: Physical Mapmentioning
confidence: 97%
“…Song et al reported the chromosomal locations of two single-copy genes, Ser-1 and CI-13, in B. mori by FISH. The results showed that Ser-1 was located near the distal end of the 11th linkage group with a relative position of 12.5±1.4 in pachytene, while CI-13 was mapped near the distal end of the second linkage group with a relative position of 8.2±1.2 in pachytene [22].…”
Section: Physical Mapmentioning
confidence: 97%
“…This paved the path to succeeding workers towards cytogenetic study of radiation induced chromosomal aberration in insects, as Carlson (1938Carlson ( , 1940Carlson ( , 1941aCarlson ( , 1941bCarlson ( , 1949, Carlson & Harrington (1955), Ray-Choudhuri (1961), Manna and Majumdar (1962,1968, Majumdar and , Kumaraswammy & Rajasekarasetty (1975, 1976, Rajasekarasetty & Kumarwaswamy (1979), Sur and Manna (1987), Sur (1998), Sur and Pandey (2004). Very recently, Song et al (2008) mapped the chromosomal locations of two single-copy genes, Ser-1 and CI-13, in silkworm (Bombyx mori) by fluorescence in situ hybridization. Even, Dutrillauxet al (2006) had reported a method for obtaining chromosome banding, from pachytene stage of the meiotic prophase in Coleopteran species, which will be of help in further cytogenetic studies by other workers.…”
Section: Introductionmentioning
confidence: 99%